MERITA STRATEGY IN PRESERVING WASTRA IN LEARNING MEDIA AS A FORM OF LOCAL CULTURE TOWARDS SOCIO-CULTURAL RESILIENCE AT SMAN 1 MALANG CITY - Meritasari, Dini Putri Ratna; Supriyono; Sukriono, Didik (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
This study examines strategies for preserving traditional wastra as a learning medium. The strategy used is the “MERITA” strategy, which consists of local content, evaluation, reaction, and integration of augmented reality (AR). This study was conducted at SMAN 1 Kota Malang with the research subjects being 10th grade students. The research method used was a qualitative approach with sources from primary and secondary sources. Primary source were obtained through interviews with students, educational media developers, and educational facilitators. Secondary sources were obtained from journals and online articels related to the topic. Data analysis was conducted using the Miles & Huberman model, which includes the stages of data collection, data reduction, and drawing conclusions. Data validity was checked through source triangulation. The research findings were as follow : first, there has been ongoing development over time regarding Wastra Nusantara, which continues to exist to this day; second, the implementation of the “MERITA” strategy in the use of Wastra educational media actively involves students in the learning process. The “MERITA” strategy is not only a learning strategy but also one of the strategies used to provide students with direct learning and practical experiences, incorporating the integration of cutting-edge technology such as augmented reality. Third, wastra media can foster social and cultural resilience through active preservation and emotional connection among students. The success of the “MERITA” strategy research on the formation of socio-cultural resilience was proven by a knowledge test on traditional wastra , namely a pre-test and post-test, with an average pre-test score of 49.55 and an average post-test score of 78.97. There was an increase in students scores after undergoing Pancasila and Citizenship Education using the “MERITA” learning strategy, which incorporates local wisdom from traditional wastra.